Genistein as Antiviral Drug against HIV Ion Channel - Sauter, Daniel; Schwarz, Silvia; Wang, Kai; Zhang, Ronghua; Sun, Bing; Schwarz, Wolfgang (Planta Medica, 2014)
Various drugs found in Chinese herbs are well known for their antiviral potency. We have tested several flavonoids with respect to their potency to block the viral protein U of the human immunodeficiency type 1 virus, which is believed to form a cation-permeable ion channel in the infected cell. We used Xenopus oocytes with heterologously expressed viral protein U as model system to test the efficacy of the drugs in voltage-clamp experiments. This method had been demonstrated in the past as a useful tool to screen drugs for their potency in inhibition of ion channel activity. The viral protein U-mediated current could be inhibited by Ba2+ with a K1/2 value of 1.6 mM. Therefore, we determined viral protein U-mediated current as current component blocked by 10 mM Ba2+. We screened several flavonoids with respect to their effects on this current. The flavonols quercetin and kaempferol, and the flavanols (−)epigallochatechin and (−)epichatechin were ineffective. The flavanone naringenin showed at 20 µM slight (about 10 %) inhibition. The most potent drug was the isoflavon genistein which exhibited at 20 µM significant inhibition of about 40 % with a K1/2 value of 81 ± 4 µM. We suggest that viral ion channels, in general, may be a good target for development of antiviral agents, and that, in particular, isoflavons may be candidates for development of drugs targeting viral protein U.
Keywords: flavonoids; genistein; HIV-1; ion channel; virus release